2013
DOI: 10.1589/jpts.25.425
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Reliability and Validity of a Newly Developed Breathing Movement Measuring Device

Abstract: Abstract.[Purpose] The purpose of this study was to test the reliability and validity of a breathing movement measuring device (BMMD) that was newly developed for the objective assessment of breathing movements in clinical practice. [Subjects and Methods] The breathing movement distances of the chest (bilateral third and eighth ribs) and abdomen (upper abdomen) of 30 healthy young males were measured using the BMMD and a threedimensional (3D) motion analysis system during quiet breathing. During measurements, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…The sample size was determined using the results of a previous study 15 that used this BMMD. The results revealed a minimal r 2 of 0.69 during QB (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The sample size was determined using the results of a previous study 15 that used this BMMD. The results revealed a minimal r 2 of 0.69 during QB (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…These results were consistent with those of the previous studies, which showed relatively lower reliability and agreement. 2,15,16 This may be explained by assuming that the differences between the 3D and BMMD distances were relatively more variable among the subjects, that is, variations in the trajectory of the left lower chest marker were relatively large.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, new instruments/devices have been proposed for measuring respiratory/breathing movement. Researchers in Sweden developed a Respiratory Movement Measuring Instrument (RMMI) [14], while researchers in Japan developed a Breathing Movement Measuring Device (BMMD) [15], [16]. These handheld devices make contact with subjects and have reported success and reliability in measuring breathing movement.…”
Section: Respiratory Signals and Motionmentioning
confidence: 99%